2010
DOI: 10.1007/s11616-010-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Geschlechtergerechte Formulierungen in Nachrichtentexten

Abstract: Zusammenfassung: Im vorliegenden Beitrag wird vergleichend analysiert, wie gut generisch maskuline Personenbezeichnungen (z. B. die studenten) und alternative geschlechtergerechte formen (z. B. die studentinnen und studenten) für Nachrichtentexte geeignet sind. Dabei ist von Interesse, ob die Verwendung der jeweiligen formen zu einem angemessenen gedanklichen Einbezug der am berichteten Ereignis beteiligten frauen führt, ob der text gut lesbar bleibt und ob das Publikum die textästhetik positiv beurteilt. Die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 12 publications
(8 reference statements)
1
17
0
5
Order By: Relevance
“…If we assume that the use of the generic masculine incorporates a reference to both migrant women and migrant men, then our results would show that migrant women are actually as visible as migrant men. However, we take the position, again supported by media effects research (Blake and Klimmt 2010), that with the use of the generic masculine form (male word endings), migrant women are always less visible than migrant men.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 83%
“…If we assume that the use of the generic masculine incorporates a reference to both migrant women and migrant men, then our results would show that migrant women are actually as visible as migrant men. However, we take the position, again supported by media effects research (Blake and Klimmt 2010), that with the use of the generic masculine form (male word endings), migrant women are always less visible than migrant men.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 83%
“…Empirical investigations have refuted this argument and have shown that text quality ( Rothmund and Christmann, 2002 ) and cognitive processing were not damaged ( Braun et al, 2007 ). When GFL texts were compared to (generic) masculine texts, there were no differences in readability and esthetic appeal ( Blake and Klimmt, 2010 ). In all, the empirical evidence does not confirm the alleged disadvantage of GFL.…”
Section: Overcoming Gender Stereotyping and Discrimination With Gendementioning
confidence: 99%
“…The next most convincing argument was that gender-fair forms are too clumsy. Research comparing German texts written with either gender-fair or GM forms in terms of readability, aesthetics, and intelligibility revealed inconclusive results: Texts with GM were either evaluated as more intelligible (Klimmt, Pompetzki, & Blake, 2008), or no differences were found regarding readability and esthetical appeal (Blake & Klimmt, 2010). Other results were that only male participants evaluated texts with GM to be more intelligible, whereas female participants evaluated both equally (Braun, Oelkers, Rogalski, Bosak, & Sczesny, 2007).…”
mentioning
confidence: 99%